Analysis of The Aiken Index to Measure The Content Validity of The Wolio Language and Culture Preservation Model Instrument - Firman Alamsyah Mansyur; Arsyad; Abdul Manaf (ELS Journal on Interdisciplinary Studies in Humanities, 2023)
This research aims to determine the content validity of the Wolio language and culture preservation model measurement instrument. This type of research is development research, using quantitative descriptive methods. The research subjects consisted of 9 experts, namely lecturers and teachers who understand the Wolio language and culture preservation model. Experts assess each item of the instrument statement. The instrument uses an ordinal rating scale and consists of 3 indicators. The collected data was analyzed using the Aiken's V formula. As a result, of the 15 instrument statement items, the content validity coefficient was greater than 0.74, indicating that all items were valid. There are 13 items in the very good category and 2 items in the good category. So this instrument is very suitable for use in measuring or assessing models of sociolinguistic preservation of language and culture.